Regulating Innate and Adaptive Immunity for Controlling SIV Infection by 25-Hydroxycholesterol - Wu, Tongjin; Ma, Feng; Ma, Xiuchang; Jia, Weizhe; Pan, Enxiang; Cheng, Genhong; Chen, Ling; Sun, Caijun (Frontiers in Immunology, 2018)
Persistent inflammation and extensive immune activation have been associated with HIV-1/SIV pathogenesis. Previously, we reported that cholesterol-25-hydroxylase (CH25H) and its metabolite 25-hydroxycholesterol (25-HC) had a broad antiviral activity in inhibiting Zika, Ebola, and HIV-1 infection. However, the underlying immunological mechanism of CH25H and 25-HC in inhibiting viral infection remains poorly understood. We report here that 25-HC effectively regulates immune responses for controlling viral infection. CH25H expression was interferon-dependent and induced by SIV infection in monkey-derived macrophages and PBMC cells, and 25-HC inhibited SIV infection both in permissive cell lines and primary monkey lymphocytes. 25-HC also strongly inhibited bacterial lipopolysaccharide (LPS)-stimulated inflammation and restricted mitogen-stimulated proliferation in primary monkey lymphocytes. Strikingly, 25-HC promoted SIV-specific IFN-γ-producing cellular responses, but selectively suppressed proinflammatory CD4+ T lymphocytes secreting IL-2 and TNF-α cytokines in vaccinated mice. In addition, 25-HC had no significant immunosuppressive effects on cytotoxic CD8+ T lymphocytes or antibody-producing B lymphocytes. Collectively, 25-HC modulated both innate and adaptive immune responses towards inhibiting HIV/SIV infection. This study provides insights into improving vaccination and immunotherapy regimes against HIV-1 infection.